PERBANDINGAN SANKSI DALAM HUKUM PIDANA NASIONAL DAN HUKUM PIDANA ADAT MINANGKABAU TERHADAP ANAK YANG MELAKUKAN PENCURIAN COMPARISON OF SANCTIONS IN MINANGKABAU'S NATIONAL CRIMINAL AND CRIMINAL LAW LAW ON CHILDREN ARE DOING THIEVES - Muhamad Syukri; Dessy Artina; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Indonesia is a country based on law. In general the source of the law that applies in Indonesia is a written law which became known as positive law. Besides that, it also applies to unwritten law which became known as customary law. Speaking about how to prosecute criminal cases committed by children, Indonesia uses Law Number 11 of 2012 concerning the Criminal Justice System. Whereas on the other hand customary law also has its way in solving child criminal cases. The author uses sociological research methods, or often called non-doctrinal theories that try to examine the effectiveness of the validity of law in society. This research is descriptive. The author describes the comparison of sanctions in national criminal law and Minangkabau customary criminal law in cases of theft by children. The results of the study are, first in the positive law of Indonesia the handling of child criminal cases is known as the diversion process, namely the settlement of child criminal cases outside the court. By customary law the handling of child criminal cases is carried out by customary deliberations. Both of these methods have their own advantages and disadvantages. To optimize the handling of criminal cases of this child, the author believes that there is a need for cooperation between the police and adat parties, so that the future is guaranteed for children who have made mistakes